(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
أثبت الفحص المصلي انتقال الإصابة الفيروسية ببذور البندورة وكانت نسبة البذور الحاملة لفيروس موزاييك الخيار وموزاييك الفصة بين 1.7-3.4%, 0.8-2.5% على التوالي في بذور المحصول السابق وكانت في بذور الهجين بين 2.3-3.0%, 0.8-1.5% على التوالي أيضاً. بلغت النسبة المئوية لانتقال فيروس موزاييك الخيار في مجموع البذور الكلي (بذور المحصول السابق + بذور الهجين) 2.4% و1.3% عند فيروس موزاييك الفصة. تم نقل الإصابة الفيروسية من البادرات بالعدوى الميكانيكية إلى مجموعة من النباتات الدالة وتنوعت الأعراض التي ظهرت بعد العدوى مثل: شفافية العروق, تحزم العروق, اختزال الأوراق, والموزاييك. أثبت اختبار بصمة النسيج النباتي المناعيTBIA وجود فيروس موزاييك الخيار وموزاييك الفصة في العينات التي حُضّر منها اللقاح وفي العينات المأخوذة من النباتات الدالة. تعدّ هذه النتيجة التسجيل الأول محلياً لانتقال فيروس موزاييك الفصة وفيروس موزاييك الخيار ببذور البندورة. Serological assay (TBIA) of tomato seedlings has proved the transmission of viral infection by Cucumber mosaic cucumovirus (CMV) and Alfalfa mosaic alfamovirus (AMV) via tomato seeds. Alfalfa mosaic ’’alfamovirus’’ and Cucumber mosaic ’’cucumovirus’’ were born in tomato seeds of the last yield in a ratio of 1.7-3.3% and 0.8-2.5% respectively, whereas the percentage of seeds transmission in tomato hybrids were 2.3-3.0% for AMV and 0.8-1.5% for CMV. The percentage of AMV and CMV transmission through total studied seeds (last yield and hybrid seeds) were 1.3% and 2.4% respectively. External symptoms showed on tomato seedlings were varied: vein clearing, vein banding, leaf deformation, and mosaic. TBIA has proved the existence of AMV and CMV in samples taken from indicator plants and from which the inoculation was prepared. To my knowledge this is the first local report of AMV and (CMV) transmission through tomato seeds.